Magnesium geochemistry of authigenic carbonate at marine cold seep - Yukai Tang; Hailong Lu; Hailong Lu; Hailin Yang (Frontiers in Marine Science, 2024)
Cold seeps, featured by their extremely methane-rich sedimentary environments, play a significant role in the geological history and are common in marine sediments across the seafloor. Primary dolomite, possibly mediated by microorganisms, can be widely discovered in methane-rich environments. Hence, cold seeps may provide new insights into the ‘dolomite problem’, which has confused geologists for decades. Magnesium isotope geochemistry of seep carbonates contributes to the understanding of the dolomite formation mechanism in marine environments. In this paper, magnesium geochemical characteristics of carbonates in modern sediments are summarized, along with rare researches on magnesium isotopes of seep carbonates. Methane vigorously interacts with sulfate by anaerobic oxidation of methane at cold seeps, producing vast amounts of dissolved sulfide which can significantly promote dolomitization of seep carbonates. Compared with temperature, alkalinity, mineralogy, etc., the competition between rapid carbonate precipitation rates and aqueous ligands may be the main factor of the magnesium fractionation at cold seeps, which is controlled by the kinetic effect. The range of magnesium isotopes of seep carbonates is narrow (from -3.46‰ to -2.36‰), and an upper limit of magnesium content seems to exist. This characteristic may be a good indicator for identifying dolomitization related to anaerobic oxidation of methane. Whereas, mechanisms of magnesium isotope fractionation and dolomitization at cold seeps remain unclear, necessitating more natural samples tested, stimulated calculation and laboratory experiment.